Suppression of ambipolar current in tunnel FETs using drain-pocket: Proposal and analysis - Garg, Shelly; Saurabh, Sneh (Superlattices and microstructures, 2018)
In this paper, we investigate the impact of a drain-pocket (DP) adjacent to the drain region in Tunnel Field-Effect Transistors (TFETs) to effectively suppress the ambipolar current. Using calibrated two-dimensional device simulation, we examine the impact of DP in Double Gate TFET (DGTFET). We demonstrate the superiority of the DP technique over the existing techniques in controlling the ambipolar current. In particular, the addition of DP to a TFET is able to fully suppress the ambipolar current even when TFET is biased at high negative gate voltages and drain doping is kept as high as the source doping. Moreover, adding DP is complementary to the well-known technique of employ-ing source-pocket (SP) in a TFET since both need similar doping type and doping concentration. •Addition of a drain-pocket adjacent to the drain region in TFETs is proposed.•Suppress the ambipolar current even at high negative VGS and high drain doping.•Complementary to source-pocket since both need same doping type & concentration.•The technique of addition of DP is general in nature.